Burnout, wellbeing and how they relate: A qualitative study in general practice trainees. Issue 3 (31st August 2022) - Prentice, Shaun; Elliott, Taryn; Dorstyn, Diana; Benson, Jill
Abstract: Purpose: Although research has explored burnout risk factors among medical trainees, there has been little exploration of the personal experiences and perceptions of this phenomenon. Similarly, there has been little theoretical consideration of trainee wellbeing and how this relates to burnout. Our study aimed to conceptualise both constructs. Method: We situated this study within a post‐positivist epistemology using grounded theory to guide the research process. Participants were recruited from one Australian General Practice training organisation. Fourteen trainees completed interviews, while a further five focus groups explored the views of 33 supervisors, educators and training coordinators. Data collection and analysis occurred concurrently, drawing upon constant comparison and triangulation. Template analysis, using an iterative process of coding, was employed to generate conceptual models of the phenomena of interest. Results: Participants described burnout as an insidious syndrome lying on a spectrum, with descriptions coalescing under seven themes: altered emotion, compromised performance, disengagement, dissatisfaction, exhaustion, overexertion and feeling overwhelmed. Wellbeing was perceived to comprise personal and professional domains that interacted and were fuelled by an underlying 'reservoir'. Both constructs were linked by the degree of a trainee's value fulfilment, with burnout occurring when a trainee's wellbeing reservoir was depleted. Conclusions: Participants in this study characterised burnout and wellbeing as multifaceted, connected constructs. Given the complexity of these constructs, preventive interventions should target both person and workplace‐focused factors, with value fulfilment proposed as the basic change mechanism. A novel model that synthesises and advances previous research is offered based on these findings. Abstract : Prentice et al. propose a novel model of burnout and wellbeing amongst General Practice trainees that is underpinned by trainees' value fulfilment.